Relaxin 2 is functional at the ocular surface and promotes corneal wound healing - Hampel, Ulrike; Klonisch, Thomas; Sel, Saadettin; Schulze, Ute; Garreis, Fabian; Paulsen, Friedrich (Investigative Ophthalmology & Visual Science, 2012)
We aimed to determine if the insulin-like peptide hormone relaxin 2 (RLN2) is expressed at the ocular surface and in tears and if RLN2 influences wound healing at the ocular surface, which is associated with extracellular matrix (ECM) remodeling.We analyzed transcript levels of human RLN2 and its cognate relaxin-like receptors RXFP1 and RXFP2 in tissues of the ocular surface, lacrimal apparatus, and human corneal (HCE), conjunctival (HCjE) and sebaceous (SC) cell lines. We analyzed effects of human RLN2 on cell proliferation and migration and quantified mRNA expression of matrix metalloproteinases (MMPs) and tissue inhibitors of metalloproteinases (TIMPs) in HCE, HCjE, and SC. Using an alkali-induced corneal wounding model, we analyzed the wound healing rate in C57BL/6 mice eyes after topically applied RLN2.The presence of RLN2, RXFP1, and RXFP2 transcripts was detected in lacrimal gland, eyelid, conjunctiva, cornea, primary corneal fibroblasts, nasolacrimal ducts, and all three cell lines. ELISA revealed RLN2 protein in all ocular surface tissues analyzed and in human tears. Stimulation of HCE, HCjE, and SC with RLN2 significantly increased cell proliferation and migration. Relative mRNA expression levels of MMP2, MMP9, TIMP1, and TIMP2 were significantly influenced by RLN2 in all three cell lines at different time points studied. The local application of RLN2 onto denuded corneal surface resulted in significantly elevated corneal wound healing.Our data support a novel role for the RLN2 ligand-receptor system at the ocular surface and in the lacrimal apparatus as a potential future therapeutic during wound healing at the ocular surface.
EVALuna2:4369